Diversity of two widespread Indo-Pacific demosponge species revisited - Erpenbeck, D.; Aryasari, R.; Benning, S.; Debitus, C.; Kaltenbacher, E.; Al-Aidaroos, A.M.; Schupp, P.; Hall, K.; Hooper, J.N.A.; Voigt, O.; De Voogd, N.J.; Wörheide, G. (Marine Biodiversity, 2017)
The Indo-Pacific is the world’s largest marine biogeographic region, covering the tropical and subtropical waters from the Red Sea in the Western Indian Ocean to the Easter Islands in the Pacific. It is characterized by a vast degree of biogeographic connectivity in particular in its marine realm. So far, usage of molecular tools rejected the presence of cosmopolitan or very widespread sponge species in several cases, supporting hypotheses on a higher level of endemism among marine invertebrates than previously thought. We analysed the genetic diversity of Hyrtios erectus and Stylissa massa, two alleged widespread sponge species of the Indo- Pacific, from the Red Sea and Mayotte in the West Indian Ocean to Polynesia in the Central Pacific. In the region of its type locality, the Red Sea, Hyrtios erectus is genetically distinct, and the populations from the remaining Indo-Pacific are a potentially different species and paraphyletic in respect to H. altus. Stylissa massa falls into different, but widespread genetic clades, one of them (Stylissa cf. massa), with distinct potentially hairpin-forming elements in mitochondrial intergenic regions. The results also indicate that morphologically established demosponge species in the Indo-Pacific can be widespread, but simultaneously harbour cryptic, genetically distinct lineages.